2016
DOI: 10.1021/acsami.6b07628
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Delivery of Extracellular ROS Based on Hematoporphyrin-Incorporated Polyurethane Film for Enhanced Proliferation of Endothelial Cells

Abstract: The principle of photodynamic treatment (PDT) involves the administration of photosensitizer (PS) at diseased tissues, followed by light irradiation to produce reactive oxygen species (ROS). In cells, a moderate increase in ROS plays an important role as signaling molecule to promote cell proliferation, whereas a severe increase of ROS causes cell damage. Previous studies have shown that low levels of ROS stimulate cell growth through PS drugs-treating PDT and nonthermal plasma treatment. However, these method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Despite the advantages, the applications of singlet oxygen-induced by the photoexcited photosensitizer have some other problems with the additional pollution of the photosensitizers themselves and unintended reactions with nonspecific materials. To solve the problems in the applications, various photofunctional materials that included photosensitizers are developed by many researchers [712]. Among them, recently, the studies have reported the bactericidal and the cell proliferation effects with the photofunctional polymers that isolate photosensitizer insides of the polymer matrix, which may provide the solution of the problems previously described.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages, the applications of singlet oxygen-induced by the photoexcited photosensitizer have some other problems with the additional pollution of the photosensitizers themselves and unintended reactions with nonspecific materials. To solve the problems in the applications, various photofunctional materials that included photosensitizers are developed by many researchers [712]. Among them, recently, the studies have reported the bactericidal and the cell proliferation effects with the photofunctional polymers that isolate photosensitizer insides of the polymer matrix, which may provide the solution of the problems previously described.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ROS are considered to be signaling molecules that lead to endothelial dysfunction during the development of AS. Ox-LDL plays an essential role in the early stages of AS by inhibiting cell proliferation, promoting inflammation, and inducing the apoptosis of endothelial cells [ 15 , 16 ]. Excessive ROS levels can lead to the apoptosis or necrosis of endothelial cells by causing irreversible damage to the DNA, proteins, RNA, and other biological molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS levels can lead to the apoptosis or necrosis of endothelial cells by causing irreversible damage to the DNA, proteins, RNA, and other biological molecules. Previous studies have shown that ROS affect cell proliferation and differentiation by directly or indirectly regulating the transcription of genes encoding cell signaling-related factors [ 15 ]. LDH, which mediates cell survival, can be considered an indicator of the degree of cell membrane damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing of intracellular ROS up to a threshold level delays cell adhesion to ECM proteins, and results in a negative function of PTP on FA development and cytoskeleton organization. We previously found that extracellular ROS increase the amount of intracellular ROS [79]. H 2 O 2 can diffuse through specific aquaporins (AQP) in the plasma membrane, and superoxide anion (O 2 – ) can penetrate the cell membrane through anion channels (Cl – channel-3) to initiate intracellular signal transduction [79,80,81,82].…”
Section: Ros-responsive Methodsmentioning
confidence: 99%
“…We previously found that extracellular ROS increase the amount of intracellular ROS [79]. H 2 O 2 can diffuse through specific aquaporins (AQP) in the plasma membrane, and superoxide anion (O 2 – ) can penetrate the cell membrane through anion channels (Cl – channel-3) to initiate intracellular signal transduction [79,80,81,82]. There are many ways in which extracellular ROS can be transported into cells, but the exact mechanism of ROS that affects cell detachment is unknown.…”
Section: Ros-responsive Methodsmentioning
confidence: 99%